منظر پھلوری کی غیر منقوط منظوم اردو کتب ِسیرت کا جائزہ: A Review of Gair Munqot Manzoom Urdu Books of Seerah by Manzar Phaloori - Asma Aziz; Anam Sattar; Umm e Aymen (Al Manhal Research Journal, 2023)
Sirah writing is a very blessed work for Muslim authors, autobiographers and poets. There is great literature of Seerah available in Urdu language in form of autobiography of Hazrat Muhammad (SAW) and poetry about him. The praising of Hazrat Muhammad (SAW) is an honor for Muslim poets. Terminologically this act is called Naat. In the Art of Sirah Writing and Naat-Goai, Ghair Manqot Manzoom/ Sante writing a very unique literature is available.Ghair Munqot Art and Literature is an unique type of literature. This literature is only linked with the languages of East i.e. Arabic, Perscian, Urdu and Punjabi languages. The study of non-dotted literature highlights its demanding and interesting nature, as authors sacrifice their time and effort to complete complex tasks and provide the world with a deeper understanding of literature. In this type of literature, those letters of language are used in writings that are free from “Noqta/ dot”. This is not very easy so it is very important that writers and poets must have a bag range of vocabulary in concerned language and synonyms are used that are free from Noqta or dots. Many writers and poets imparted to produce their contribution in this field. This research deals with the review of Manzar Phalowri’s Ghair Manqot books of Naat i.e i. Walli Lolak ii. Mah-e-jira iii. Arham-e-Alam. This research helps to highlight that this work is the valuable and quality literature of their respective fields.